Short-Term Effect of Air Pollution on Daily Hospital Visits for Anxiety Disorders in Southern China with Low Pollution Concentrations - Xinyuan Zhong; Tingting Guo; Jianghui Zhang; Qiong Wang; Rong Yin; Kunpeng Wu; Qing Zou; Meng Zheng; Brian J. Hall; Andre M. N. Renzaho; Kangning Huang; Wen Chen (Toxics)
The global prevalence and burden of anxiety disorders (ADs) are increasing. However, findings on the acute effects of air pollution on ADs remain inconclusive. We evaluated the effects of short-term exposure to ambient air pollutants, including fine particulate matter (PM2.5), inhalable particulate matter (PM10), nitrogen dioxide (NO2), carbon monoxide (CO), sulfur dioxide (SO2), and ozone (O3), on daily hospital visits for ADs. A generalized additive model was used to perform a time-series analysis on data from a Southern China city’s medical insurance system between 1 March 2021, and 31 July 2023. Although the daily levels of most pollutants (PM10, SO2, CO, NO2 and O3) were consistently below China and WHO’s Ambient Air-Quality Standards, significant associations were observed between daily hospital visits for ADs and all six air pollutants. Each interquartile range increase in concentrations resulted in the largest odds ratios of 1.08 (95% CI: 1.01, 1.16) at lag1 for PM2.5, 1.19 (95% CI: 1.05, 1.34) at lag07 for NO2, 1.14 (95% CI: 1.05, 1.23) at lag02 for CO, 1.12 (95% CI: 1.01, 1.25) at lag07 for PM10, 1.06 (95% CI: 1.01, 1.12) at lag7 for SO2 and 1.08 (95% CI: 1.01, 1.15) at lag7 for O3, respectively. The effects of NO2 and CO remained robust across subgroup analyses and sensitivity analyses. Females and middle-aged individuals showed stronger associations than other subgroups. The findings underscore the necessity for public health efforts to alleviate the impact of air pollution on mental health, even in low-concentration settings.